2010
DOI: 10.6004/jnccn.2010.0127
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Task Force Report: Specialty Pharmacy

Abstract: The use of specialty pharmacies is expanding in oncology pharmacy practice. Specialty pharmacies provide a channel for distributing drugs that, from the payor perspective, creates economies of scale and streamlines the delivery of expensive drugs. Proposed goals of specialty pharmacy include optimization of pharmaceutical care outcomes through ensuring appropriate medication use and maximizing adherence, and optimization of economic outcomes through avoiding unwarranted drug expenditure. In oncology practice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…50 The National Comprehensive Cancer Network (NCCN) has also commented on specialty pharmacies and their effects on patient care and medication safety regarding chemotherapy. 53 Regulatory oversight. Regulatory agencies have a responsibility to review product packaging, labeling, and advertising to ensure that their content accurately reflects safety and efficacy data and conforms with language that has been approved by the FDA.…”
Section: Recommendations For Manufacturers and Regulatory Agenciesmentioning
confidence: 99%
“…50 The National Comprehensive Cancer Network (NCCN) has also commented on specialty pharmacies and their effects on patient care and medication safety regarding chemotherapy. 53 Regulatory oversight. Regulatory agencies have a responsibility to review product packaging, labeling, and advertising to ensure that their content accurately reflects safety and efficacy data and conforms with language that has been approved by the FDA.…”
Section: Recommendations For Manufacturers and Regulatory Agenciesmentioning
confidence: 99%
“…[19][20][21][22][23] In general, patients utilizing specialty community pharmacies receive more personalized care and have better adherence rates compared with those in nonspecialty community pharmacies. 15,[24][25][26][27] A pilot study found that Medi-Cal beneficiaries with HIV who received medication therapy management (MTM) in community pharmacies that specialized in providing HIV-intensive MTM services had higher adherence rates that persisted over 3 years, compared with patients in pharmacies not providing these services. 24,25 Although the dispensing of 90-day prescription supplies in community pharmacies is generally increasing, mail order pharmacy may be appropriate for PLWH who are stabilized on therapy and comfortable with their medication regimens, and may be more attractive than community-based pharmacy services for those patients who prefer online ordering of medication.…”
Section: Opinions Of a Small Sample Of Pharmacists About Pharmacymentioning
confidence: 99%
“…12 Health plans may require use of specialty pharmacy distribution channels for costly medications associated with complex management issues, including medication adherence, because of a belief that the "high-touch" services offered by specialty pharmacies (e.g., patient education, identification of sources of financial assistance) provide a therapeutic benefit to the patient. [13][14][15][16][17] Of the 74% of employers that offered a specialty pharmacy benefit in May 2011, 48% required specialty drugs to be channeled through a designated specialty pharmacy (either community-based or mail order). 6 Similarly, 14 ADAPs used central pharmacy distribution, and 18 ADAPs had designated ADAP pharmacies for pick-up in June 2010.…”
Section: Opinions Of a Small Sample Of Pharmacists About Pharmacymentioning
confidence: 99%
“…These challenges have been widely noted in national reports and publications addressing the complexity of coordinating care among diverse practice settings in which specialty pharmacy services are provided separately from the health system. 3 Therefore, health systems have a unique opportunity to serve as the central hub for patient care and research for patients with complex illnesses. A comprehensive health systembased specialty pharmacy program can provide numerous benefits to patients.…”
mentioning
confidence: 99%